Providers′ knowledge, attitude and dispensing practices of E-Pills in government dispensaries of south district in Delhi, India - Kishore Vertika; Misro Man; Nandan Deoki (Wolters Kluwer Medknow Publications, 2010)
Background: South Delhi is one of the well developed districts in the capital with best public health care facilities. Knowledge, attitude and dispensing practices of emergency contraceptive pills (E-pills) were assessed among health care providers of government dispensaries in South Delhi. Study Design: A descriptive epidemiological study. Materials and Methods: Both medical and paramedical (n = 428) providers in 63 government health care facilities were interviewed between August to December 2007 using a semi-structured interview schedule. Results: Among the different categories of the providers, medical officers were observed to be most knowledgeable about E-pills and the pharmacists were the least. The correct prescribed dose of E-pill was known only to 32% of the providers while 49% knew about its right time of intake. Misconceptions and apprehensions for promoting its use were very much prevalent even among medical officers as majority felt that open access to E-pills would increase promiscuity. The dispensing practice of providers was found positively ( P < 0.05) correlated with their knowledge. Training resulted a significant ( P < 0.05) improvement in knowledge, attitude and dispensing practice of the providers. Knowledge and training combined together contributed 35% to the dispensing practice (R 2 = 0.35). Conclusion: Besides knowledge, behavior change communication strategies should form a part of the training curricula of health care providers that would help to improve the dispensing practice of E-pills.